Differential involvement of trigeminal transition zone and laminated subnucleus caudalis in orofacial deep and cutaneous hyperalgesia: the effects of interleukin-10 and glial inhibitors - LaGraize Stacey C; Zou Shiping; Wang Hu; Guo Wei; Shimizu Kohei; Iwata Koichi; Wei Feng; Dubner Ronald; Ren Ke (SAGE Publishing, 2009)
Abstract Background In addition to caudal subnucleus caudalis (Vc) of the spinal trigeminal complex, recent studies indicate that the subnuclei interpolaris/caudalis (Vi/Vc) transition zone plays a unique role in processing deep orofacial nociceptive input. Studies also suggest that glia and inflammatory cytokines contribute to the development of persistent pain. By systematically comparing the effects of microinjection of the antiinflammatory cytokine interleukin (IL)-10 and two glial inhibitors, fluorocitrate and minocycline, we tested the hypothesis that there was a differential involvement of Vi/Vc and caudal Vc structures in deep and cutaneous orofacial pain. Results Deep or cutaneous inflammatory hyperalgesia, assessed with von Frey filaments, was induced in rats by injecting complete Freund's adjuvant (CFA) into the masseter muscle or skin overlying the masseter, respectively. A unilateral injection of CFA into the masseter or skin induced ipsilateral hyperalgesia that started at 30 min, peaked at 1 d and lasted for 1-2 weeks. Secondary hyperalgesia on the contralateral site also developed in masseter-, but not skin-inflamed rats. Focal microinjection of IL-10 (0.006-1 ng), fluorocitrate (1 μg), and minocycline (0.1-1 μg) into the ventral Vi/Vc significantly attenuated masseter hyperalgesia bilaterally but without an effect on hyperalgesia after cutaneous inflammation. Injection of the same doses of these agents into the caudal Vc attenuated ipsilateral hyperalgesia after masseter and skin inflammation, but had no effect on contralateral hyperalgesia after masseter inflammation. Injection of CFA into the masseter produced significant increases in N-methyl-D-aspartate (NMDA) receptor NR1 serine 896 phosphorylation and glial fibrillary acidic protein (GFAP) levels, a marker of reactive astrocytes, in Vi/Vc and caudal Vc. In contrast, cutaneous inflammation only produced similar increases in the Vc. Conclusion These results support the hypothesis that the Vi/Vc transition zone is involved in deep orofacial injury and suggest that glial inhibition and interruption of the cytokine cascade after inflammation may provide pain relief.